Pengaruh Lama Perkecambahan terhadap Karakteristik Fisikokimia dan Fungsional Tepung Kecambah Kacang Komak (Lablab Purpureus (L.) Sweet) - Cahayani Putri, Ni Ketut Emi; Wisaniyasa, Ni Wayan; Sri Wiadnyani, Anak Agung Istri (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 13 No 2 (2024): Jurnal ITEPADO - 10.24843/itepa.2024.v13.i02.p03, 2024)
Komak beans are one type of legume that has a fairly high nutritional content such as carbohydrates, protein and crude fiber. One of the efforts to improve the quality of the komak bean is through the germination process. Fresh sprouts have a very low shelf life and a limited variety of consumption. Processing sprouts into sprout flour is an alternative to extend the shelf life of sprouts. This research aims to determine the effect of germination time on the characteristics physicochemical and functional of Komak Bean flour ((Lablab purpureus (L.) sweet), as well as to determine the germination time that can produce characteristics. This research used a Complete Randomized Design. with germination duration treatment consisting of 4 levels, which is 0 hours, 24 hours, 36 hours, 48 hours, and 60 hours. The experimental was repeated 3 times to resulting 15 experimental units. The data obtained were analyzed using an analysis of variance and if treatment had a significant effect, it was followed by a Duncan Multiple Range Test.The results showed that germination time had a very significant effect on rendement, L value (brightness level), a value (green-red color), moisture content, ash content, protein content , and crude fiber. Germination time also had a significant effect on b value (blue-yellow color), fat content, carbohydrate content, water absorption, swelling power and solubility, but had no significant effect on bulk density and oil absorption. The best characteristic of the flour in this study was komak bean sprout flour that has been germination time of 60 hours with rendement 75.38%, bulk density 0.61 g/ml, L* value 38.92, a* value 9.03, value b* 17.94, moisture content 2.71%, ash content 3.68%, fat content 5.34%, protein content 23.75%, carbohydrate content 35.48%, crude fiber 8.45%, absorption water 2.64 ml/g, oil absorption 3.41 ml/g, swelling power 18.32 g/g, and solubility 19.50%.